2013
DOI: 10.5713/ajas.2013.13178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <italic>Bacillus Subtilis</italic>-based Direct-fed Microbials on Immune Status in Broiler Chickens Raised on Fresh or Used Litter

Abstract: Type of dietary direct-fed microbials (DFMs) or poultry litter could directly influence the composition of gut microbiota. Gut microbiota plays an important role in shaping the developing immune system and maintaining the homeostasis of the mature immune system in mammal and chickens. The present study was carried out to investigate the interaction among litter, DFMs and immunity in broiler chickens exposed to a field-simulated environment. Immune status of broiler chickens was assessed by serum antibodies aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
(38 reference statements)
0
23
1
Order By: Relevance
“…In addition to their effects on healthy animals, Bacillus DFMs also have been shown to ameliorate the deleterious outcomes associated with enteric bacterial infections of poultry. B. subtilis dietary supplementation reversed the effects of Clostridium perfringens infection on decreased growth performance and alterations in the intestinal microbiota, compared with unsupplemented controls (24). In a C. perfringens/Eimeria maxima coinfection model of avian necrotic enteritis, feeding of B. subtilis reduced gut pathology and animal mortality, and restored alterations in the intestinal microbiome, compared with controls (22).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition to their effects on healthy animals, Bacillus DFMs also have been shown to ameliorate the deleterious outcomes associated with enteric bacterial infections of poultry. B. subtilis dietary supplementation reversed the effects of Clostridium perfringens infection on decreased growth performance and alterations in the intestinal microbiota, compared with unsupplemented controls (24). In a C. perfringens/Eimeria maxima coinfection model of avian necrotic enteritis, feeding of B. subtilis reduced gut pathology and animal mortality, and restored alterations in the intestinal microbiome, compared with controls (22).…”
Section: Discussionmentioning
confidence: 92%
“…We previously reported that dietary supplementation of broiler chickens with B. subtilis-based DFMs increased body weight gains, compared with unsupplemented controls (21). Further, chickens fed a B. subtilis-containing diet had increased intestinal villus height and crypt depth, augmented mitogen-and antigen-induced spleen cell proliferation, greater macrophage phagocytosis of Salmonella bacteria, decreased serum levels of α-1-acid glycoprotein and nitric oxide, altered expression of cytokine genes (interferon-γ, interleukin-1β, CXCL2) in intestinal lymphocytes, and a modified CD4 + /CD8 + ratio of peripheral blood lymphocytes (24)(25)(26)(27)(28). The current study extends these prior results to now demonstrate that dietary supplementation with B. subtilis 1781 or B. subtilis 787 alters the chicken intestinal metabolome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of A. hookeri on crucial phenotypes of broiler chickens were investigated, given the importance of growth trait enhancement without antibiotics for growth promotion (AGPs) and to decrease the risk of antibiotic resistance [36]. Other studies investigated feed supplements using natural foods including extracts from herb species, which enhanced poultry health by improving immunity and protecting chickens from avian diseases [37][38][39][40][41][42][43][44]. Our previous study has shown that broiler chickens supplemented with A. hookeri show improved growth performance [22].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely accepted alternatives include probiotics, prebiotics, exogenous enzymes, and phytogenics including plant extracts in poultry. In addition, the novel concept which employs the natural enhancement of host immunity by alternatives has been gained much interest as a coccidiosis control measure in broiler chickens ( Lee et al, 2011 ; Lee et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%